1984
DOI: 10.1159/000115727
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the Blink Reflex in Infants

Abstract: The blink reflex was elicited in 50 children from birth to 3 years of age. In the awake state, the R1 response was always obtained; R2 responses, especially contralateral ones, were more difficult to elicit under 9 months of age. R1 latency and VIIth motor nerve conduction variations were a good witness of the peripheral nervous system maturation. The influence of the different states of waking and sleeping on these reflex responses was studied. These results and some of the mechanisms that underlie these chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…As the peripheral components for the processing of acoustic signals are not appreciably different between these two groups of infants, the most likely etiology for this difference in response lies in the brainstem pathway. (Vecchierini-Blineau and Guiheneuc, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…As the peripheral components for the processing of acoustic signals are not appreciably different between these two groups of infants, the most likely etiology for this difference in response lies in the brainstem pathway. (Vecchierini-Blineau and Guiheneuc, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…There is great variability in the blink reflex for pre-term infants, neonates, and children of different ages [15][16][17][18][19][20] . Other physiological conditions influencing blink responses are: sleep-wake cycles 19,[21][22][23] , auditory stimulation 24 , attention and cognitive tests 25,26 , conditioning stimulation 26 , and habituation 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…We observed a decreased eyeblink amplitude in quiet (non-REM) as compared to active (REM) sleep in the infants. Vecchierine-Blineau and Guiheneuc (26) showed that different states of waking and sleeping in adult and infant subjects influenced the second component of the blink reflex, causing a more pronounced depressed response during quiet sleep in the infant, and suggested the polysynaptic reflex arc may be subject to an inhibitory influence at the level of the reticular formation during non-REM sleep.…”
Section: Discussionmentioning
confidence: 99%